Wheelchair Users' Perspective on Transportation Service Hailed Through Uber and Lyft Apps. Issue 5 (May 2023) - Gebresselassie, Mahtot
Numerous lawsuits have been filed against Uber and Lyft for lack of disabled accessibility of the transportation service they facilitate, with some of the lawsuits focusing on wheelchair accessibility. The paper investigates accessibility from the perspective of wheelchair users and examines their perceptions, experiences, and preferences. Some of the experiences of wheelchair users have been documented in grey literature. The study investigates these in addition to dimensions that are currently unexplored: their perceptions and preferences. A survey of 341 wheelchair users in the U.S. was conducted to understand general trends and patterns. Data collected from 224 complete and 117 partial responses were analyzed using descriptive statistics and linear and logistic regressions. The findings indicate that more than 50% of respondents were satisfied with the service, but nearly 40% experienced service denial. Almost half of those without Uber or Lyft experience perceive Uber and Lyft as a viable means of transportation. The study also showed that the propensity to be an Uber or Lyft user is associated with type of wheelchair, having access to a vehicle, and level of education. The purpose of the study is to bring to the fore the lived experiences of wheelchair users by taking a larger sample than anecdotal references in media reports—where most of the current debate on this topic resides—and to gain new insights. The study fills the gap in academic literature by developing a new knowledge. It also outlines recommendations relevant for practice and policy considerations.